Statistical Analysis of Adhesive Bond Parameters in a Single Lap Joint System - Anjum, Asraar; Syed Mohamed Ali, Jaffar; Mohamed Zayan, Jalal; Aabid, Abdul (Zeal Press, 2020)
The design and sizing of adhesives used for bonding of two or mo re similar/dissimilar materials in aerospace and automobile structural engineering studies ha ve always been important. A vast number of studies ha ve reported via experimental, numerical, and analytical methods of lap joint system with adhesive bonding. Optimization studies of the adhesives used in joints are highly necessary which can be done either with numerical or experimental data in determining the suitable parameters for the specified solution through the design of experiments analysis . In this study, a single lap joint with different variables has been modelled and the resulting stres s was measured in each case. A standard two dimensional plane stress element was use d for modelling of single lap joint str ess elements. Furthermore, a statistical analysis method was used to optimize the selected parameters for the improvement of current solutions with suitable parameters. The results showed that the response values of stresses were influenced by input parame tric variables which control the stresses and reduces the risk of damage to the adhesive bonds used in the joints. Moreover, based on the present optimization results it has been found that the thick adhesive bond will result in higher shear stress transfe r with less width and suitable for the lower applied voltage.